Improving global health security through implementation of the National Action Plan for Health Security in Sierra Leone, 2018-2021: lessons from the field - Charles Njuguna; Mohamed Vandi; Tushar Singh; Ian Njeru; Jane Githuku; Wilson Gachari; Robert Musoke; Victor Caulker; Joseph Bunting-Graden; Michael Mahar; Sydney Morgan Brown; Mohamed Alpha Bah; et al. (BMC, 2023)
Abstract Background All countries are required to implement International Health Regulations (IHR) through development and implementation of multi-year National Action Plans for Health Security (NAPHS). IHR implementation requires annual operational planning which involves several tools such as NAPHS, State Party Annual Report (SPAR), Joint External Evaluation (JEE) and WHO IHR Benchmarks tool. Sierra Leone has successfully improved IHR capacities across the years through successful annual operational planning using the above tools. We conducted a study to document and share the country's unique approach to implementation of NAPHS. Methods This was an observational study where the process of implementing and monitoring NAPHS in Sierra Leone was observed at the national level from 2018 to 2021. Data was obtained through review and analysis of NAPHS annual operational plans, quarterly review reports and annual IHR assessment reports. Available data was supplemented by information from key informants. Qualitative data was captured as notes and analysed for various themes while quantitative data was analyzed mainly for means and proportions. Results The overall national IHR Joint External Evaluation self-assessment score for human health improved from 44% in 2018 to 51% in 2019 and 57% in 2020. The score for the animal sector improved from 32% in 2018 to 43% in 2019 and 52% in 2020. A new JEE tool with new indicators was used in 2021 and the score for both human and animal sectors declined slightly to 51%. Key enablers of success included strong political commitment, whole-of-government approach, annual assessments using JEE tool, annual operational planning using WHO IHR Benchmarks tool and real time online monitoring of progress. Key challenges included disruption created by COVID-19 response, poor health infrastructure, low funding and inadequate health workforce. Conclusion IHR annual operational planning and implementation using evidence-based data and tools can facilitate strengthening of IHR capacity and should be encouraged.